Halal Tourism Potential:An Investigation In Bromo Tengger Indonesia - Rizal Joesoef, Jose (2019)
The purpose of this research is to identify the potential of halal tourism destinations in Bromo Tengger by reviewing Attraction and Amenity variables. This research is a descriptive research with a quantitative approach. It used Primary data collection by using a questionnaire given to Moslem tourists aged 17 years old and they are originally from outside Bromo Tengger area. The sample of 250 was determined by sampling technique, which was then analysed in a descriptive and multivariate biplot exploratory analysis. The research findings show that amenity has quite big potential to support the realization of halal tourism in Bromo Tengger tourism destinations which is then followed by attraction variable. In general, it can be said that the brand building of Bromo Tengger's halal tourism destinations still requires greater assessment and efforts so that all indicators of halal tourist destinations can be fulfilled.